Orientation-Induced Effects of Water Harvesting on Humps-on-Strings of Bioinspired Fibers - Chen, Yuan (Sci Rep, 2016)
Smart water-collecting functions are naturally endowed on biological surfaces with unique wettable microstructures, e.g., beetle back with “alternate hydrophobic, hydrophilic micro-regions”, and spider silk with wet-rebuilt “spindle-knot, joint” structures. Enlightened by the creature features, design of bio-inspired surfaces becomes the active issue in need of human beings for fresh water resource. Recently, as observed from spider web in nature, the net of spider silk is usually set in different situations and slopes in air, thus spider silks can be placed in all kinds of orientations as capturing water. Here, we show the styles and orientations of hump-on-string to control the ability of water collection as bioinspired silks are fabricated successfully. As different strings, sizes (height, length, pitch) of humps can become the controlling on volumes of extreme water drops. It is related to the different solid/liquid contact regions resulting in the as-modulated wet adhesion due to orientations of humps-on-strings. The conversion of high-low adhesion can be achieved to rely on orientations for the effect of capturing water drops. These studies offer an insight into enhancement of water collection efficiency and are helpful to design smart materials for controlled water drop capture and release via conversions of high-low adhesion.